A Life Span Developmental Perspective on Psychosocial Development in Midlife. Issue 1 (10th April 2019) - Kuther, Tara L.; Burnell, Kaitlyn
Abstract : Research in life span development suggests that middle adulthood is a time of stability, discovery, and psychosocial growth. This review applies the life span developmental perspective to advance counselors' understanding of psychosocial development during middle adulthood, specifically, midlife adults' sense of self, perceptions of aging, developmental tasks, and contexts.